A The Formulation And Stability Formulation And Stability Testing Of Lotion From Ethanol Extract Pagoda Flower (Clerodendrum Paniculatum L.) And Rhizomes Key Find (Boesenbergia Rotunda (L.) Mansf.) As Antioxidant - Barus, Bunga Barus (Jurnal Penelitian Farmasi Dan Herbal, 2024)
Unhealthy lifestyles and air pollution can cause the number of free radicals in the body to increas. The formation of free radicals is a widely accepted important mechanism that causes skin aging. For this reason, the body needs antioxidants that can neutralize very dangerous free radicals. A plant whose efficacy as an antioxidant has been proven is the pagoda flower plant. Another plant used to ward off free radicals is the rhizome of Temu Kunci (Boesenbergia rotunda (L.) Mansf.) which is from the Zingiberaceae family which has compounds that have the potential to act as antioxidants. This research aims to formulate a lotion preparation of pagoda flower extract and ginger root rhizome extract as well as carrying out a stability test of the preparation and determining the IC 50 value using the DPPH method. The research used the maceration method with 96% ethanol. Then the extract is formulated into a lotion with varying concentrations of pagoda flower extract: ginger rhizome extract, namely: F1(1:1); F2(2:1); F3(1:2). The preparations of pagoda flower extract lotion and ginger root rhizome extract were eval_uated for organoleptic tests, pH tests, homogeneity tests, viscosity tests and hedonic tests and antioxidant tests were carried out with a wavelength of 516nm. The results of the research on pagoda flower extract lotion and ginger root rhizome extract have met the requirements for organoleptic tests, pH test, homogeneity test, and viscosity test. The IC50 value of the lotion preparation of ethanol extract of pagoda flowers and ethanol extract of ginger rhizome showed a strong category (50-100) with an IC50 value of F1 86.13 µg/ml, F2 73.91 µg/ml and F3 75.83 µg/ml.